2005
DOI: 10.1007/s11218-004-5489-2
|View full text |Cite
|
Sign up to set email alerts
|

Students? knowledge about the value of discussions for teaching and learning

Abstract: We are particularly interested in looking at teaching and learning from students' perspectives. Focussed interviews and written responses from a number of linked investigations with middle-school and tertiary students highlighted that students perceive discussion to be a valuable teaching -learning technique. This paper provides text extracts, organised into six key themes, to illustrate students' understandings about how discussion helps them to learn. We conclude that, across the whole participant group, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…10, No. 10;2017 stimulate students to reveal that there are no wrong answers, so that students believe in themselves or on the answer that they wrote, and (c) explore the question to the student through group discussions (Askell-Williams & Lawson, 2005) and gives the example of stimulus (Zohar, 2004).…”
Section: The Implementation Of Carousel Feedback and Round Tablementioning
confidence: 99%
See 2 more Smart Citations
“…10, No. 10;2017 stimulate students to reveal that there are no wrong answers, so that students believe in themselves or on the answer that they wrote, and (c) explore the question to the student through group discussions (Askell-Williams & Lawson, 2005) and gives the example of stimulus (Zohar, 2004).…”
Section: The Implementation Of Carousel Feedback and Round Tablementioning
confidence: 99%
“…Increasing HOTS can be done by asking questions, group discussion, peer tutoring, and cooperative learning (Karabulut, 2012;King et al, 2011;Askell-Williams & Lawson, 2005;Kauchak & Eggen, 1998). Increasing HOTS using Carousel Feedback cooperative learning model can be initiated by familiarizing the students with the activity of observing, discussing, rotating teams, analyzing the work of other groups and providing feedback.…”
Section: The Implementation Of Carousel Feedback and Round Table For mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the language of the questionnaire items was straightforward, and although the strategies, such as 'discussions' or 'draw pictures or diagrams' or 'ask a question' might be enacted in different ways by younger or older students, our interpretation is that each strategy type was sufficiently clear, such that both younger and older students could recognise whether they did, or did not, use that strategy type. In our previous interview research with school students, questions such as these have been interpreted in the ways that we intended (e.g., Askell-Williams & Lawson, 2005a;2005b (2008) have argued that growth in strategy knowledge requires appropriate metacognitive activity, so that the generation of more precise knowledge about strategy effectiveness will be stimulated by performance monitoring and by linking the outcomes of monitoring to the prior strategy knowledge (Winne, 1996).…”
Section: Cognitive Strategy Usementioning
confidence: 99%
“…With respect to task values and participation in discussion, Askell-Williams and Lawson (2005) found that middle school students and prospective teachers believed that discussion helped them learn, yet participants had a limited view of the purpose of discussions. The authors suggested the importance of teaching explicitly about the pedagogical purpose of engaging in discourse in conjunction with teaching subject matter content to prospective teachers.…”
Section: Prospective Teachers' Motivationmentioning
confidence: 99%